Use of Linezolid in the treatment of surgical infectious complications under antibiotic resistance (Perioperaciina Medicina, 2021)
Linezolid – a first representative of the new class of synthetic antibiotics oxazolidones. Its antibacterial spectrum includes Gram-positive microorganisms, including multi-resistant strains. Its unique mechanism of action conditions absence of cross-resistance with other antibiotics. This drug is presented in peroral and parenteral forms. Unlike vancomycin, it has optimal pharmacokinetic profile. Linezolid was approved by Food and Drug Administration (FDA) in 2000 for the treatment of the following diseases: hospital- and community-acquired pneumonia, skin and soft tissue infections with or without complications caused by Gram-positive bacteria, vancomycin-resistant enterococci and pneumococcal meningitis, caused by penicillin-resistant Streptococcus pneumoniae.
Keywords: Linezolid; vancomycin-resistant enterococci (VRE); methicillin-resistant Staphylococcus aureus (MRSA)